Resistance of Lactobacillus fermentum InaCC B1295 Encapsulated in Microcrystalline Cellulose from Palm Leaf Waste to Acidic Conditions Across Various Temperatures and Storage Durations" - Firdaus, Royyan; Kasim, A; Kasim, F (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2024)
Lactobacillus fermentum InaCC B1295 is a probiotic bacterium with limited tolerance to acidic environments, bile fluids, and high temperatures, necessitating physical protection via microcrystalline cellulose (MCC) encapsulation derived from palm leaf waste. This study aimed to evaluate the resistance of encapsulated probiotic bacteria under acidic conditions at various temperatures and storage durations to identify the optimal storage temperature. A factorial complete randomized design (CRD) with two factors was employed: storage temperature (room temperature, 4°C, and -18°C) and storage time (0, 7, 14, 21, 28, 35, and 42 days). The results indicated that storage time and the interaction between storage time and temperature significantly affected the total lactic acid bacteria (LAB) count. However, temperature alone and its interaction with storage time did not significantly impact the percentage reduction in the number of encapsulated Lactobacillus fermentum InaCC B1295 at pH 2. Overall, encapsulated bacteria stored at various temperatures demonstrated comparable bacterial resistance..